Madam Secretary - Albright, Madeleine 1937-2022; Woodward, Bill (Miramax Books, 2003)
The highest-ranging woman in the hisotry of U.S. government chronicles the story of her life, from her childhood as a Czechoslovakian refugee through her rise to power in the world of international diplomacy and policy-making, detailing her two terms as Secretary of State, her personal life, and the colorful personalities she met along the way.